مساهمة إمام زركشي في تعليم اللغة العربية : مساهمة إمام زركشي في تعليم اللغة العربية - Zuhrotul Mufidah (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2021)
Imam Zarkasyi combining the system of school and madrasa system into a modern cottage with learning system intensive Arabic language in it, success in teaching Arabic able to produce alumni who also has attention in the development of the Arabic language in Indonesia. The success of the Imam Zarkasyi attract researchers to further uncover what's behind his success, so that the formulation of the problem posed: 1. How is the life of Imam Zarkasyi to become an expert in Arabic? 2.How the mindness and struggle of Imam Zarkasyi in education Arabic ? The conclusion of researchers based formulation of the problem is: Imam Zarkasyi a lot to gain experience in learning Arabic in various areas, especially when studying with Alhasyimi in Solo and Mahmud Yunus in Padang, and among the thoughts of Imam Zarkasyi is the method of learning the Arabic language in Indonesia, learning Arabic in Islamic boarding schools in Indonesia, the activities in improving the ability of Arabic language and spirit of teachers in learning Arabic. And among the struggle of Imam Zarkasyi is in writing books Arabic systematic is now widely used in several educational institutions in Indonesia, building a modern cottage with a system of learning Arabic intensive therein, and his struggle to produce alumni who play a role in the community, especially in learning Arabic in Indonesia.